2007
DOI: 10.1177/0048393107307663
|View full text |Cite
|
Sign up to set email alerts
|

Complexity Theory, Systems Theory, and Multiple Intersecting Social Inequalities

Abstract: This article contributes to the revision of the concept of system in social theory using complexity theory. The old concept of social system is widely discredited; a new concept of social system can more adequately constitute an explanatory framework. Complexity theory offers the toolkit needed for this paradigm shift in social theory. The route taken is not via Luhmann, but rather the insights of complexity theorists in the sciences are applied to the tradition of social theory inspired by Marx, Weber, and Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
268
0
41

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(310 citation statements)
references
References 41 publications
1
268
0
41
Order By: Relevance
“…In recent years, Luhmann's domination of social systems theory has been challenged by a growing number of social theorists, in particular realists, who reject his rather abstract and virtual notion of the system (Bunge 2004;Elder-Vass 2007b;Pickel 2007;Walby 2007;Wan 2011b). Their main charge is that by disregarding the distinction between the elements and the whole system, Luhmann ends up with holism, where the whole is more important than the parts (Wan 2011a: 40).…”
Section: Systems In Social Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, Luhmann's domination of social systems theory has been challenged by a growing number of social theorists, in particular realists, who reject his rather abstract and virtual notion of the system (Bunge 2004;Elder-Vass 2007b;Pickel 2007;Walby 2007;Wan 2011b). Their main charge is that by disregarding the distinction between the elements and the whole system, Luhmann ends up with holism, where the whole is more important than the parts (Wan 2011a: 40).…”
Section: Systems In Social Theorymentioning
confidence: 99%
“…Of course these multilayered system dynamics may operate in nonlinear, potentially chaotic ways; they serve not to regulate the system -maintaining its equilibrium -but rather change both its composition (continually blurring the system/environment boundary) and its dynamism (Walby 2007). For example, the securitisation of migration since 2001 shows how what may once have been seen as a factor external to any migration system between West Africa and Europe, is now incorporated within it.…”
Section: What Do New Advances In Systems Theory Have To Offer Migratimentioning
confidence: 99%
“…I can only briefly note some of the ways in which it has been conceived here. The idea that gender, race and class are distinctive systems of subordination with their own range of specific social relations (Williams 1989;Weber 2001) is found in a range of work (see also Walby 2007 for the application of complexity theory). On the other hand gender, race and class may be treated as different ideological (e.g.…”
mentioning
confidence: 99%
“…Whilst people with dementia have traditionally been assumed to lack agency, the research showed how women with dementia convey a 'sense of agency' within their relationships, albeit constrained by gendered norms and expectations (see Kabeer 1999). Thus, this study has highlighted the need for a multidimensional approach to researching everyday life in dementia which takes account of intersectionality, in order to develop a more enriched understanding of the social factors that facilitate or constrain women's agency (see Walby 2007). The study also demonstrated the value of facilitating the research participation of people with significantly impaired speech and/or more advanced dementia.…”
Section: Resultsmentioning
confidence: 93%